The The Significance of Using the Dinar and Dirham as Currencies in the Islamic Economy: Analysis of Weaknesses and its Benefits - Meirison, Meirison; Febrianto, Sucipto; Hendra, Testru (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2023)
This article intends to describe today's feasibility of using the dinar and dirham currencies in the Islamic economic system. The application of Dinar and Dirham is considered more appropriate because they have a fixed value and guarantee stability. The dinar and Dirham currencies are deemed capable of solving currencies, such as coping with massive inflation in the world currency system. Dinar and Dirham can realize the stability of exchange rates and increase international trade progress, especially in Islamic countries throughout history. The author analyzes books from the library with a descriptive analysis approach. In theory, dinars and dirhams stabilize a country's finances if supported by production factors. This will accelerate the turnaround of money and the economy. However, the Dinar and Dirham also do not escape various problems. For example, the large hoarding of gold and silver, the obstacles between a country, the possibility of a monopoly by a government with more gold reserves, and very high production capabilities.